PEMBIAYAAN SISTEM BAGI HASIL LEMBAGA KEUANGAN SYARIAH PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KABUPATEN JEMBER - Jauhar, Mohammad Dio Awaludin; Roziq, Ahmad (Jurnal Ekonomi Akuntansi dan Manajemen, 2019)
This study aims to know the implementation of ?pembiayaan bagi hasil? conducted by the islamic financial institutions including the type of financing given outcomes, the problems during the implementation from the islamic financial instituitons and partners view. This study is a qualitative research with multi-case studies approach, the research examines two or more subjects, background, or storage of research data. Stages of research conducted field study/survey is used to find the problem of financing system in Islamic Financial Institutions and their partners. The result shows that overall of seven islamic financial institutions have ?pembiayaan bagi hasil? and Musyarakah financing as one of their products in providing services to their business partners. But it its implementation, there are three main problems, they are  the lack of financial statement reports, the side streams, and asymetry of information. From the problem, researches gives some solutions, the first is the partner need a mentoring about financial statement report periodically, raise public awareness about honesty culture, and improve the quality and quantity of human resources on islamic financial institutions. Keyword: Profit Loss Sharing, Islamic Financial Institutions, SMEs